Partisipasi Komunitas dalam Mitigasi Urban Heat Island (UHI) di Desa Daenaa - Lydia S. Tatura; Rahmayanti; Syafriani; Niniek Pratiwi (Journal of Applied Social Science, 2025)
Urban Heat Island (UHI) is a phenomenon of increased microclimatic temperature in densely populated areas due to the lack of vegetation and high anthropogenic activities. The Community Service Program (KKN) in Daenaa Village, Gorontalo, aims to empower the community in mitigating UHI through a participatory approach. The implementation method includes environmental education, vertical greening training, and the creation of micro-architectural elements such as vertical gardens and pocket parks. This study uses a descriptive-qualitative approach with field observations, interviews, and activity documentation. The results show an increase in community awareness of micro-environmental issues and the formation of the